Prospects in development of quality rice for human nutrition - Se, C.H.; Khor, B.H.; Karupaiah, T., (Penerbit Universiti Kebangsaan Malaysia, 2015)
Rice in the human diet serves underprivileged populations in Asia as a means of nutritional replenishment for energy and protein as well serving as a vehicle for micronutrient fortification. About 85% of rice consumption is mainly white rice. A possible relationship between white rice consumption and health risk exists. The threat is real enough for the scientific community to promote wholegrain consumption in place of refined grains. In the transitioning food environment, white rice is categorised as a refined grain and is thus implicated in the development of non-communicable diseases (NCDs). There is considerable interest in exploring glycaemic index (GI) in relation to the consumption of different rice varieties. The variable glycaemic response to rice types is better appreciated from the viewpoint of factors that moderate this response. Genetic make-up, physicochemical properties, amylose and dietary fibre content, post-harvesting processing as well as cooking methods are influential factors in determining GI variability. To date, new rice varieties bio-fortified with micronutrients such as iron, zinc and beta-carotene have been produced and useful in ameliorating the micronutrient deficiencies such as iron deficiency anaemia, stunted growth and xerophthalmia affecting children or adults in developing countries. Rice breeding and improvement programs play a major role in safeguarding the food environment, by taking into account traits that will improve rice quality in terms of GI as well as micronutrient capacity.